NETWORKS OF ANTHROPOCENTRIC LINGUISTICS (Scientific journal of the Fergana State University, 2024)
As science and technology develop in the world, any science has its own precise and effective research methods. Among them, the most important, primary function of the science of linguistics is to reveal the secrets of communication between people. It can be said that even grammatical knowledge may be secondary. Bringing communicative qualities to the center of research can give new approaches to the science of linguistics, which requires a change in the composition of its terms. By changing the object of investigation of the science of linguistics from the language material, which is a product of human thought, to the study of the person himself, its issues become acutely relevant for society. The degree of relevance of linguistics departments will also change.Descriptive, differential semantic and hermeneutic techniques were used to carry out the study.The results of the study serve to effectively change the approach of linguistics to learning issues. It put forward the idea that the pragmatic goal is primary in Language Research.As a conclusion of the study, a table of scientific directions is developed, which is part of the anthropocentric paradigm. In addition, serious theoretical opinions on the importance of language levels have been expressed in terms of the point at which language is directed towards the expression of a pragmatic goal.